Religious Values of Chefs in Bali and Food Waste Awareness: A Preliminary Study - Bhaskara, Gde Indra (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
This study examines the perspectives of chefs in Bali on the influence of religion on their attitudes towards food waste management. This research is the initial research of a project called Environmental habitus of chefs and food waste minimization in restaurant kitchens. Environmental habitus of chefs and food waste minimization in restaurant kitchens itself has two main categories to study, namely Past and Current Period. This study focuses on Past event, which in this case is religious value as one of the other factors such as at home education, out of home education and on the job training. The sample studied was five chefs, and analyzed using a qualitative method approach. The result of this preliminary study is religious value to a greater or lesser extent affect the view of the chefs on their habit regarding to food waste management in kitchen’s restaurant.